The Tradition of Shalawatan at The Majelis Ahababul Musthafa in Surakarta: A Study Of The Living Qurâ€™an Sura Al-Ahzab (33) 56 - Mohamad Nuryansah (Jurnal Penelitian, 2020)
This research aims to examine the internalization of sura al-Ahzab (33): 56 contained of the command for Muslims in reciting shalawat to prophet Muhammad for the Majelis Shalawat Ahbabul Musthafa and its relation to the social-religion in Surakarta by using sociological approach, especially functionalism theory. The research findings show that the role of Ahbabul Musthafa to the social-religion is divided into: a) for the members of Ahbabul Musthafa; 1) give a well-religious concept; 2) close of relationship each others; 3) lay to the Ulamaâ€™ generation; 4) create a piety and good moral community; 5) think out the responsibility people both in our environment and others: b) for the Muslims; 1) to be a well-behaved media of religious proselytizing and refuse all of radicalism and terrorism; 2) become an umbrella organization to share the idea, experiences and to discuss the religious and the nationality problem, such as build a patriotism; 3) to be a religious information center. The others, the strategy of Ahbabul Musthafa to overcome the strained situation and the diversity of social-religion constellation can be seen through the paradigm followed by it. This calls â€œfind the fundamental similarity as a Muslims and avoid furuâ€™ problemsâ€.